Assessing the Fitness of Physiotherapy Postgraduate Students Coping with the Future Job Demand. - Pavana; Srinivas M.; Pruthviraj R. (Indian Journal of Physiotherapy & Occupational Therapy)
Background & purpose: Physical fitness is a state of health and well-being and, more specifically, the ability to perform aspects of sports, occupations, and daily activities. Physical fitness is generally achieved through proper nutrition, moderate-vigorous physical exercise and sufficient rest. The study's objectives were to measure the upper limb and lower limb flexibility, strength of upper limb, lower limb and aerobic fitness of the Postgraduate students in Bengaluru using tests and to assess the coping of Postgraduate physiotherapy students towards the job demands, physical exercise and fitness. Method: This study included subjects between the ages of 21 -- 30 years of physiotherapy postgraduate students. Subjects were recruited based on inclusion and exclusion criteria. It was a descriptive cross-sectional study of 117 subjects. Demographic data were collected, Nordic musculoskeletal questionnaire, Physical Activity Readiness - questionnaire (PAR-Q) and Physiotherapy student occupational health and safety questionnaire was used, and BMI, skinfold, waist to hip ratio, shoulder flexibility test, sit and reach test, push-up test, single leg wall sit test and Harvard step test were used to find the level of physical fitness. Results: Self-perceived fitness level among 117 subjects was 16.2% good, 68.4% moderate, and 15.4% poor. It was observed that the prevalence of neck trouble in the last 12 months was 50.42%, trouble during the last 7 days was 34.18 %, and ADL affected in the last 12 months was 13.67%. Conclusion: The present study showed that self-perceived fitness was moderate level, and health-related fitness evaluation findings showed poor fitness among physiotherapy postgraduate students. There was the highest prevalence of musculoskeletal disorders at the neck. The musculoskeletal pain seen among postgraduate students may affect their task performance and hinder work efficiency.